Airway Clearance Strategies in Cystic Fibrosis and Non-Cystic Fibrosis Bronchiectasis - Main, Eleanor; Grillo, Lizzie; Rand, Sarah (Seminars in Respiratory and Critical Care Medicine, 2015)
Many patients with cystic fibrosis (CF) and non-CF bronchiectasis present with common symptoms in clinical domains that appear to benefit from airway clearance strategies. These symptoms include chronic productive cough, retention of excessive, purulent mucus in dilated airways, impairment of normal mucociliary clearance (MCC), atelectasis, breathlessness, fatigue, respiratory inflammation, fever, infection, and airflow obstruction. Airway clearance strategies may involve singular and focused interventions for the purpose of removing secretions and improving lung recruitment and gas exchange in patients with atelectasis. Strategies may also involve indirect or adjunctive interventions that facilitate or enhance effective airway clearance at different ages or stages of the disease process, for example, inhalation therapy, exercise, oxygen therapy, or noninvasive ventilation. The aim is to optimize care by selecting any one or combination of these in responding intelligently and sensitively to individual and changing patient requirements during their lifetime. Currently, a solid evidence base does not exist for airway clearance strategies in CF and non-CF bronchiectasis, and much of airway clearance clinical practice remains in the domain of clinical expertise. The paucity of evidence is partly explained by the relatively immature research machinery in allied health care internationally but is also partly to do with inadequate or inappropriate research designs. This article aims to provide an overview of the nature of, and physiological basis for, the direct and indirect airway clearance strategies in CF and non-CF bronchiectasis with reference to the best available evidence.
Keywords: physiotherapy (techniques); cystic fibrosis; bronchiectasis; respiratory; breathing exercises; inhalation therapy; positive pressure respiration; rehabilitation